Landslide susceptibility of the Prato–Pistoia–Lucca provinces, Tuscany, Italy. Issue 1 (4th November 2016) - Segoni, Samuele; Tofani, Veronica; Lagomarsino, Daniela; Moretti, Sandro
ABSTRACT: We mapped landslide susceptibility in the provinces of Lucca, Pistoia and Prato (central Italy), a 3103 km 2 territory that approximately corresponds to the portion of Tuscany principally affected by landslides. We used a methodology based on a treebagger random forest. The input parameters used for the susceptibility assessment are curvature, flow accumulation, topographic wetness index, elevation, profile curvature, planar curvature, slope gradient, aspect, land use and lithology. The map was validated providing satisfactory results (AUC = 0.84). The map classifies the study area into four susceptibility classes that identify areas with different probabilities of being affected by landslides. TheMain Map represents a useful instrument to assist land planning, development of mitigation measures and landslide risk management. Moreover, it could be used in further research addressing quantitative hazard and risk assessment.